PO:01:014 | Differential inflammatory responses of CD14+ and CD14– synoviocytes in psoriatic arthritis: implications for pathogenesis and targeted therapies: Monia Maccaferri1, Monica Montanari2, Francesco Zambianchi3|4, Carlo Salvarani1|5, Elisa Pignatti1|4 | 1Dipartimento CHIMOMO; 2Dipartimento di Scienze e Vita; 3Dipartimento SMECHIMAI Università di Modena e Reggio Emilia; 4Azienda Ospedaliero Universitaria di Modena; 5Struttura Complessa di Reumatologia, Azienda Unità Sanitaria Locale di Reggio Emilia-IRCCS, Italy - di Reumatologia, Società Italiana (Reumatismo, 2025)
Background. Investigating the inflammatory response of synoviocytes in patients with psoriatic arthritis (PsA) is crucial due to their central role in disease pathogenesis. Recent studies have reported upregulation of interleukin-6 (IL-6) and activation of the transcription factor NF-κB as key mechanisms in PsA development. Although the role of dendritic-like CD14 synoviocytes remains unclear, these cells have been shown to contribute to the initiation and maintenance of inflammation. Furthermore, impaired dendritic cell function has been associated with dysregulated inflammatory responses that may promote chronic inflammation. Therefore, this study aimed to explore the molecular responses of non-dendritic CD14 synoviocytes under basal conditions and after stimulation with inflammatory mediators, and to characterize the basal molecular profile of CD14 synoviocytes. Materials and Methods. Fibroblast-like synoviocytes (FLS) were isolated from synovial membranes of healthy donors (h) and PsA patients. CD14 FLS were selected using immunomagnetic beads and cultured under basal conditions (wt), whereas CD14 FLS were stimulated for 24 hours with LPS and IFNγ. Cells were analyzed at passage 6 (P6) by real-time PCR. Healthy donor FLS were also analyzed by flow cytometry (FACS) at passages 2 (P2) and 6 (P6) for CD90 and CD14 expression. Results. Under basal conditions, healthy CD14 FLS (h-FLS CD14 ) exhibited higher CD64 expression than PsA CD14 FLS. Following inflammatory stimulation, h-FLS CD14 showed increased expression of all analyzed genes compared to PsA-FLS CD14 , except for HLA-DR (Fig. 1). In PsA-FLS CD14 , expression of macrophage-associated markers (CD14, Mer-TK, CD64) decreased, whereas all other genes were upregulated except CD90, CDH-11, and NF-κB (Fig. 2). FACS analysis prior to selection revealed that h-FLS wt at P2 consisted of CD14 /CD90 (67%), CD14 /CD90 (3%), and CD14 /CD90 (8%) populations. Upon activation, the CD14 /CD90 population remained nearly unchanged (64%), while CD14 /CD90 (5%) and CD14 /CD90 (15%) subsets increased. After magnetic selection and expansion (P6), h-FLS CD14 wt were predominantly CD14 /CD90 (93%), with minimal CD14 /CD90 (0.8%) and CD14 /CD90 (0.01%) populations (Fig. 3). Conclusions. The differential expression of surface markers and inflammatory genes between h-FLS and PsA-FLS highlights distinct responses to inflammatory stimuli. The higher expression of pro-inflammatory markers in h-FLS CD14 suggests a stronger inflammatory capacity compared with PsA-FLS CD14 , whereas PsA-FLS CD14 display a more inflammatory phenotype under basal conditions. These findings underscore the dynamic nature of synovial cell populations in response to inflammation and indicate that detailed phenotypic characterization of synoviocytes is essential for developing more effective therapeutic strategies in PsA management. Moreover, elucidating the phenotypic differences between CD14 and CD14 synoviocytes may aid in identifying novel biomarkers for early diagnosis and personalized treatment of PsA.